An Alliance for Accelerated Change: Food system solutions at the nexus of agriculture, environment, and nutrition - Strategy 2020–2025 - Alliance of Bioversity International and CIAT (Bioversity International and the International Center for Tropical Agriculture, 2019)
Our planet – both humans and the natural world – faces four global crises of relevance to the Alliance of Bioversity International and the International Center for Tropical Agriculture (CIAT): climate change, biodiversity loss, environmental degradation, and the so-called triple burden of malnutrition – hunger, nutrient deficiencies, and overnutrition. Food systems are both a victim of these crises – climate change, for example, is driving down productivity of agricultural systems around the world – and a culprit – with agriculture and related land uses accounting for 23 percent of human greenhouse gas emissions and a major driver of habitat and biodiversity loss. But this doesn’t have to be so. The Alliance of Bioversity International and CIAT is a new venture created to turn food and agriculture systems around. This, the Alliance’s first unified strategy, combines the strengths of the two organizations – including genebanks, use and conservation of agricultural and tree biodiversity, climate-smart agriculture, nutrition, digital agriculture, crop improvement, and participatory research approaches – to develop solutions to these crises, through a clear focus on working at the nexus of agriculture, environment, and nutrition. The strategy has been designed from the outset for impact at scale, from local to global levels, through a range of partnerships and new business models that change our relationships with key development actors from next users to partners, co-investors, and clients. We have a vision of food systems and landscapes that sustain the planet, drive prosperity, and nourish people. To achieve this, our mission is to deliver research-based solutions that harness agricultural biodiversity and sustainably transform food systems to improve people’s lives in a climate crisis. We will achieve our mission through four strategic objectives: 1. People consume diverse, nutritious, and safe foods. 2. People participate in and benefit from inclusive, innovative, and diversified agri-food markets. 3. People sustainably manage farms, forests, and landscapes that are productive and resilient to climate change. 4. Communities and institutions sustainably use and safeguard agricultural biodiversity.